2011
DOI: 10.1183/09031936.00076210
|View full text |Cite
|
Sign up to set email alerts
|

A mouse GM-CSF receptor antibody attenuates neutrophilia in mice exposed to cigarette smoke

Abstract: We investigated the role of granulocyte-macrophage colony-stimulating factor (GM-CSF) in a subchronic exposure model of cigarette smoke (CS)-induced inflammation using antibodies directed against GM-CSF or the GM-CSF receptor (GM-CSFR) a-chain.CS-induced mononuclear and neutrophilic inflammation following 4 days of CS exposure in BALB/c mice was assessed in bronchoalveolar lavage (BAL) fluid. An increase in mature dendritic cells (DCs) (CD11c+ and major histocompatibility complex II+) and Gr-1-high neutrophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
21
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 40 publications
7
21
2
Order By: Relevance
“…Despite the accumulation of phospholipids, we observed no difference in the recruitment of immune cells in anti-GM-CSF-treated animals. This observation is in contrast to previous reports, showing that GM-CSF blockade attenuated inflammatory processes [17,23]. This is probably a consequence of the dose of antibody used in the current study, which was substantially lower than that previously used to inhibit inflammatory processes.…”
Section: Figurecontrasting
confidence: 55%
See 1 more Smart Citation
“…Despite the accumulation of phospholipids, we observed no difference in the recruitment of immune cells in anti-GM-CSF-treated animals. This observation is in contrast to previous reports, showing that GM-CSF blockade attenuated inflammatory processes [17,23]. This is probably a consequence of the dose of antibody used in the current study, which was substantially lower than that previously used to inhibit inflammatory processes.…”
Section: Figurecontrasting
confidence: 55%
“…This is probably a consequence of the dose of antibody used in the current study, which was substantially lower than that previously used to inhibit inflammatory processes. This suggests that, in addition to the previously documented role in neutrophil recruitment [17,23], GM-CSF activates mechanisms involved in the processing of damaged lipids following smoke exposure.…”
Section: Figurementioning
confidence: 94%
“…In experimental animals, exposure to cigarette smoke consistently upregulates MMP-12 production and release [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]; this phenomenon appears to be much more frequent than upregulation of any other MMP, although we make that statement with caution because MMP-12 has been examined much more frequently than other MMPs.…”
Section: Mmps In Emphysema: Mmp-12mentioning
confidence: 67%
“…BOTELHO et al [10] showed that smoke upregulated production of granulocyte macrophage colony-stimulating factor (GM-CSF) in mice and that an antibody to GM-CSF or its receptor prevented smoke-mediated increases in MMP-12 release, while at the same time decreasing neutrophil and dendritic cell influx. Similar results using anti-GM-CSF antibodies were reported by VLAHOS et al [18], who also noted that antibody treatment decreased production of TNF-a and the chemokine MIP-2, without decreasing MMP-9 production.…”
Section: Mmps In Emphysema: Mmp-12mentioning
confidence: 99%
“…MMPs have shown to be critically involved in all these processes [16,17], and in particular phenotypes presenting with the overlap of asthma and COPD are associated with risk alleles of variant MMP genes with differences in the expression of their gene products [18,19].…”
mentioning
confidence: 99%